2021
DOI: 10.1186/s42269-021-00548-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the extraction method on polyphenols, flavonoids composition and anti-hyperlipidemic properties of papaya leaves (Carica papaya Linn.)

Abstract: Background Papaya (Carica papaya Linn.) is well known for its nutritional as well as medicinal value. Different parts of the plant including leaves have been used as therapeutic remedies for various diseases. The objective of the present study is to determine the impact of different extraction methods; microwave-assisted, ultrasonic-assisted and conventional maceration on extract yield, polyphenols, flavonoids composition and subsequently, the anti-hyperlipidemic potential of papaya leaves (Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…Therefore, the current study can be valuable in further assessing quantitative parameters of phytotherapeutically active molecules. The total flavonoid content was highest in ethanol extract as compared to methanol and aqueous extracts, which correlates with previous studies [ 32 , 33 ]. These findings confirm that C. papaya leaves contain a significant quantity of flavonoid compounds, which exert an anti-inflammatory effect.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the current study can be valuable in further assessing quantitative parameters of phytotherapeutically active molecules. The total flavonoid content was highest in ethanol extract as compared to methanol and aqueous extracts, which correlates with previous studies [ 32 , 33 ]. These findings confirm that C. papaya leaves contain a significant quantity of flavonoid compounds, which exert an anti-inflammatory effect.…”
Section: Discussionsupporting
confidence: 91%
“…The most abundant polyphenols in papaya leaf were gallic acid, caffeic acid, and rutin. In addition, catechin, naringenin, and chlorogenic and syringic acids have also been identified in leaf extracts [35]. We found that the aqueous methanol extraction resulted in a higher amount of polyphenols compared to pure water extracts.…”
Section: Discussionmentioning
confidence: 66%
“…Rutin, a predominant flavonoid in C. papaya leaves, has traditionally served as a chemical marker for quality control [ 38 , 45 ]. In addition to rutin, gallic acid has also been identified as another phenolic acid compound that offers a reliable indicator for product standardization [ 46 ]. Importantly, several of these compounds, particularly rutin, quercetin, and gallic acid, have been reported to exhibit potent anti-oxidant properties [ 47 ].…”
Section: Discussionmentioning
confidence: 99%